Intensification of Heat Transport from the Furnace to Heat Accumulator through a Phase Change - Milan Malcho; Stanislav Gavlas; Peter Hrabovsky; Roman Banovcan; Tomas Puchor; Lukasz Orman; Tadeas Ochodek (Communications - Scientific letters of the University of Zilina, 2017)
In the article the authors analyse the process of heat transport from the furnace to a heat accumulator through a phase change of a heat carrier (working substance), design a construction and describe measurements done on experimental equipment. This type of heat transport is substantially more intense that the one in natural or forced convection and takes place without generating the working substance flow with a drive aggregate. Another advantage is heat accumulation control according to a pre-set temperature of an accumulator through an automatic flow control of the working substance in a condensation phase. The equipment consists of an autonomous evaporation section, a heat accumulator integrated with a condensation heat exchanger and of a thermostatically operated valve with thermal drive.